Bcr-Abl regulates osteopontin transcription via Ras, PI-3K, aPKC, Raf-1 and MEK - Hickey, Fionnuala B; England, Karen; Cotter, Thomas G (My University, 2005)
Chronic myeloid leukemia (CML) is caused by the constitutively active Bcr-Abl tyrosine kinase. This fusion protein is generated by the Philadelphia translocation t(9;22). CML is a progressive condition that invariably advances from a drug-sensitive to a drug-resistant, aggressive, acute leukemia. The mechanisms responsible for this progression are largely unknown; however, in many cases, progression is accompanied by an increase in Bcr-Abl expression. Osteopontin (OPN) expression has been shown to be involved in the progression and increased aggression and invasiveness of many solid tumors. Here, we demonstrate that OPN expression is induced in a model of leukemia, and we describe the identification of specific signaling pathways required for the induction of OPN expression by p210 Bcr-Abl. We have determined that high levels of Bcr-Abl activate a signaling cascade involving the sequential activation of Ras, phosphatidylinositol-3 kinase, atypical protein kinase C, Raf-1, and mitogen-activated protein kinase kinase, leading to the ultimate expression of OPN. Our results suggest that these molecules represent a single pathway and also that there is no redundancy in this pathway, as inhibition of any individual component results in a block in the induction of OPN. The data presented here define for the first time the ability of Bcr-Abl to stimulate the expression of OPN and also identify the signaling pathway involved. This may not only prove important in understanding the mechanisms of progression of CML but also highlights a pathway that may prove significant in many other cases of oncogenesis, where OPN expression is implicated.
PUBLISHED
Keywords: chronic myeloid leukemia